“Away, come away”: Moving dead women and Irish emigration in W. B. Yeats’s early poetry - Simpson, H (Presses universitaires de Rennes, 2017)
Emigration and Ireland are closely entwined in cultural consciousness, yet little scholarly work addresses Irish emigration in W. B. Yeats’s poetry. I use the lens of Irish emigration to tackle another under-discussed phenomenon in Yeats’s early poetry: the physically moving, dead, female body. In the latter half of the nineteenth century, young unmarried women were emigrating from Ireland in historically unprecedented numbers, and this high emigration rate of Irish women parallels the recurrence of moving dead or supernatural women in Yeats’s pre-1900 poetry.